Optical excitation and detection of neuronal activity. Issue 3 (7th November 2018) - Hu, Chenfei; Sam, Richard; Shan, Mingguang; Nastasa, Viorel; Wang, Minqi; Kim, Taewoo; Gillette, Martha; Sengupta, Parijat; Popescu, Gabriel
Abstract : Optogenetics has emerged as an exciting tool for manipulating neural activity, which in turn, can modulate behavior in live organisms. However, detecting the response to the optical stimulation requires electrophysiology with physical contact or fluorescent imaging at target locations, which is often limited by photobleaching and phototoxicity. In this paper, we show that phase imaging can report the intracellular transport induced by optogenetic stimulation. We developed a multimodal instrument that can both stimulate cells with subcellular spatial resolution and detect optical pathlength (OPL) changes with nanometer scale sensitivity. We found that OPL fluctuations following stimulation are consistent with active organelle transport. Furthermore, the results indicate a broadening in the transport velocity distribution, which is significantly higher in stimulated cells compared to optogenetically inactive cells. It is likely that this label‐free, contactless measurement of optogenetic response will provide an enabling approach to neuroscience. Abstract : Quantitative phase imaging enables label‐free detection of enhanced intracellular activities induced by optogenetic stimulation.